Transcription Factor-7-Like-2 (TCF7L2) in Atherosclerosis: A Potential Biomarker and Therapeutic Target - Li, Junyi; Zhou, Li; Ouyang, Xinping; He, Pingping (Frontiers in Cardiovascular Medicine, 2021)
Transcription factor-7-like-2 (TCF7L2), a vital member of T-cell factor/lymphoid enhancer factor (TCF/LEF), plays a manifold role in human normal physiological and pathological processes. TCF7L2 shows multiple anti-atherosclerosis effect by activating certain molecular mechanisms, including regulation of metabolism balance, macrophage polarization, neointimal hyperplasia. A Single-nucleotide substitutions (SNP) of TCF7L2-rs7903146, a genetic high-risk factor for type 2 diabetes, is susceptible to cardiovascular disease as a link between metabolism disorder and atherosclerosis. In this review, we summarize the anti-atherosclerosis effect and novel mechanisms of TCF7L2 to elaborate a potential anti-atherosclerosis biomarker and provide a therapeutic target for cardiovascular diseases.